Catholics and Pentecostals: Canons 844 and 1124 - Wellens, Stephanus (Roman replies and CLSA advisory opinions 1997, 1997)
Pentecostals were once considered individuals within various churches who lacked systematic teaching and who simply wished to return to the practices of the early Church. However, in recent years they have formed Pentecostal communities and churches, published systematic teaching, and even established Pentecostal universities. Catholic canonists must now address the following questions: (1) Is baptism administered in Pentecostal churches valid? (2) Are Catholic ministers permitted to administer the sacraments of penance, the Eucharist, and the anointing of the sick to baptized Pentecostals who are in danger of death or in grave necessity (c. 844, §4)? (3) Could the conditions for a dispensation be fulfilled when a Catholic wishes to marry a baptized Pentecostal?